Bio controlled efficacy of Bacillus thuringiensis cry protein protection against tomato fruit borer Helicoverpa armigera in a laboratory environment. (May 2022) - Chandrakasan, Gobinath; Ayala, Manuel Toledano; García Trejo, Juan Fernando; Marcus, Gabriel; Maruthupandy, Muthuchamy; Kanisha, C. Chenthis; Murugan, Manavalan; AL-mekhlafi, Fahd A.; Wadaan, Muhammad A.
Abstract: Bio-pesticides that utilize beneficial microbial agents represent a new option that can potentially reduce reliance on chemical pesticides. To facilitate control of crop pests, this study includes both selection and characterization of Bacillus thuringiensis strains based on Cry gene content and toxicity evaluation. The result is an effective and non-hazardous polyphagous lepidopteran pest controller, Helicoverpa armigera . To achieve this objective, we selected ten soil bacteria samples selected from 10 different agricultural regions in Queretaro State, Mexico. Certainly, 65 and 130 kDa protein bands were observed in SDS-PAGE analysis of spore-crystal mixtures. Efficacy of bio-pesticides, 4 g/L effective water yielded maximum mortality; a mean of 64.88% of tomato fruit borer larvae were eliminated. The PCR sequences of bacterial strain were characterized and showed 98–99% similarity shows the distance from comparison of the 16S rRNA gene sequences of Bacillus thuringiensis. Highlights: Comparative effect of natural and semi synthetics diet on Helicoverpa armigera. Luria Bertani agar medium was suitable for the formation of maximum number of colonies. Microbial formulation using Bacillus thuringiensis was prepared as bio-pesticide. Insect cadavers analyzed for the endotoxin protein by SDS-PAGE and strains were characterized.